Cyclic Nucleotides and Phosphodiesterases in Platelets - Haslam, Richard J.; Dickinson, Natalie T.; Jang, Elliott K. (Thrombosis and Haemostasis, 1999)
It is now almost 30 years since the discovery that prostaglandin E1 (PGE1) inhibits platelet responses to aggregating agents, together with finding that the effects of this compound are mediated by adenosine 3′, 5′-cyclic monophosphate (cAMP) initiated interest in the physiological and pharmacological regulation of platelet function by other agents that increase platelet cAMP, as reviewed elsewhere.1 The most important agonists that stimulate cAMP formation in platelets have now been identified as prostacyclin (PGI2), prostaglandin D2 (PGD2), and adenosine, which exert their effects through receptors of the serpentine or seven transmembrane segment class (IP, DP and A2 receptors, respectively).2 The latter then stimulate cAMP formation by adenylyl cyclase via the GTP-dependent activation of the G-protein, Gs (Fig. 1). In the classical view, cAMP exerts its effects solely by binding to the RI and RII regulatory subunits of type I and type II cAMP-dependent protein kinases (PKA). The catalytic subunits of the kinases then dissociate and phosphorylate selected serine and threonine residues on target proteins that prevent or reverse platelet activation.2 A crucial role is played by cAMP phosphodiesterases, which degrade cAMP to 5′-AMP, thereby diminishing and terminating the effects of agonists that stimulate cAMP formation (Fig. 1). In early studies, this was demonstrated by the ability of first-generation inhibitors of cAMP phosphodiesterases, particularly the methylxanthines, to inhibit platelet aggregation and potentiate the inhibitory effects of activators of platelet adenylyl cyclase.1 Such studies provided the rationale for the subsequent development of more potent and selective phosphodiesterase inhibitors as potential antithrombotic agents.Interest in the role of guanosine 3′,5′-cyclic monophosphate (cGMP) in platelets closely followed the discovery of the inhibitory action of cAMP. An early hypothesis that cGMP might potentiate platelet aggregation was abandoned by 1978, after it was shown that some inhibitors of platelet aggregation, such as nitroprusside (NP), also increased platelet cGMP.1 It soon emerged that all nitrovasodilators release nitric oxide and activate soluble guanylyl cyclase (GC) and that the cGMP formed stimulates cGMP-dependent protein kinases (PKG) in many cells and tissues (Fig. 1), including vascular smooth muscle and platelets.3 The crucial physiological importance of this pathway was established with the identification of endothelium-derived relaxing factor (EDRF) as nitric oxide.4 cGMP phosphodiesterases play an essential role by limiting increases in cellular cGMP, and inhibition of these enzymes was found to potentiate the effects of nitric oxide and nitric oxide donors on platelets and other cells.5The ability of cAMP and cGMP to activate distinct protein kinases led to a persistent view that these two cyclic nucleotides operate in parallel and independent ways to inhibit platelet function, cAMP mediating the effects of agonists such as PGI2, and cGMP mediating the effects of nitric oxide.2,3 However, over the last 10 years, considerable evidence has accumulated to indicate that this is not the case in platelets (or in many other cells) and that cross-talk between the cAMP and cGMP systems may occur on at least two levels, affecting both cyclic nucleotide phosphodiesterase (PDE) and protein kinase activities (Fig. 1). One of the most significant of these interactions is through the effects of cGMP on the hydrolysis of cAMP by PDEs. It is the purpose of this chapter to describe platelet PDEs and to discuss how their individual characteristics and regulation may impact platelet function and the design of useful antithrombotic agents. In addition, evidence that both cGMP and cAMP may activate PKG and that these cyclic nucleotides may exert effects in platelets that do not involve either PKA or PKG will be discussed briefly.